Do Individual Employees’ Learning Goal Orientation and Civic Virtue Matter? A Micro-Foundations Perspective on Firm Absorptive Capacity - Yao, Fiona K.; Chang, Song (Strategic Management Journal, 2017)
[Research summary: In this study, we build on the micro-foundations perspective and investigate how individual characteristics contribute to the development of firm absorptive capacity. In particular, we assess how individual learning goal orientation affects firm potential and realized absorptive capacity. Furthermore, we study how individuals’ civic virtue acts as a micro-level social integration mechanism that moderates the effect from firm realized absorptive capacity to potential absorptive capacity. Using the multilevel structural equation modeling technique and data from 871 core-knowledge employees nested in 139 high-technology firms, we find support to our major hypotheses. Together, this study finds support for the micro-foundations’ perspective and generates novel insights on how individual-level factors could be linked with firm-level heterogeneity in absorptive capacity. Managerial summary:We study how employees’ characteristics contribute to a firm’s absorptive capacity, that is, the ability of a firm to identify, assimilate, and exploit knowledge from the environment. Because firms have increasingly tapped into external resources to foster innovation over the past two decades, absorptive capacity is crucial to firm learning and success. Using data from 871 core-knowledge employees in 139 high-technology firms, we find that individual employees’ learning goal orientation, the tendency to seek improvements in employees’ competence and to understand or master new things advances the development of a firm’s potential and realized absorptive capacity. More important, individual employees’ civic virtue, the discretionary involvement in company issues, serves as a social integration mechanism that reduces the gap between firm potential and realized absorptive capacity.]